Pengaruh Aktivitas Pemasaran Terhadap Profitabilitas dan Nilai Perusahaan Perusahaan Makanan, Minuman, dan Rokok - Mariana - (Business Accounting Review, 2015)
This study aimed to examine the influence partially or simultaneusly of Marketing Activity which was consisted of Marketing Expense, Company Age, and Company Size toward Profitability which was represented by Return on Sales, Return on Asset toward Market Value which is represented by Earning per Share, and Market to Book Value Ratio. This study used the annual report of Food, Baverage, and tobacco Companies listed in BEI in 2008-2013 as secondary data. The samples used in this study were 100 annual reports. The results revealed that Marketing Expense affected ROA, EPS, and MBVR significantly. Company Size only affected EPS and MBVR. Company Age affected significantly ROS, ROA, and MBVR.